Cross-linked piperidine anion exchange membrane for alkaline electrolytic cell and preparation method thereof
Through the structure and preparation method of the crosslinked piperidine anion exchange membrane, the problem of easy degradation of anion exchange membrane in an alkaline environment is solved, high conductivity and chemical stability are achieved, and the requirements of industrial applications are met.
Patent Information
- Application Number
- CN202411346839.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing anion exchange membranes are prone to degradation in an alkaline environment, resulting in a decrease in ion conductivity and loss of mechanical strength, which cannot meet the requirements of long-term industrial use.
Using the structure of a crosslinked piperidine anion exchange membrane, the cross-linking of branched groups containing piperidine structure and linear structure polymerization units, combined with quaternization reagents and initiators, prepare high chemical stability and electrical conductivity rate of membrane.
It improves the chemical stability and conductivity of the membrane, meets the long-term use of alkaline electrolytic cells, and provides better performance and durability.
Smart Images

Figure CN118854368B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by water electrolysis, and in particular relates to a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell and a preparation method thereof. Background Art
[0002] Faced with the trend of global energy structure transformation towards low-carbonization and the environmental challenges brought about by the current dominance of fossil energy, promoting the application of clean energy has become a core demand of energy reform in various countries. Traditional clean energy such as tidal energy, wind energy, solar energy and other renewable energy are limited by natural conditions and cannot output energy continuously and stably, and cannot be used directly by people. Hydrogen, as a clean energy carrier, is considered to be a key factor that plays an important role in the future energy system. Water electrolysis is a major method for producing green hydrogen, especially when the electricity used comes from the above renewable energy sources.
[0003] Different water electrolysis technologies have their own advantages. For example, alkaline water electrolysis (AWE) is mature but its efficiency needs to be improved. Proton exchange membrane (PEM) technology has a fast response speed but high cost, while solid oxide water electrolysis (SOEC) is limited by the operating temperature. As an emerging branch of AWE technology, AEM (anion exchange membrane) technology combines the advantages of high efficiency and low cost with its ability to work under alkaline conditions. It also further reduces the overall cost of the system by using non-precious metal catalysts, making it a key technology to meet the development needs of future energy systems.
[0004] The anion exchange membranes (AEMs) that have been developed generally use similar engineering plastics such as polysulfone and polyetheretherketone as the main chain. For example, a Chinese invention patent application discloses a cross-linked polyetheretherketone anion exchange membrane for fuel cells and a preparation method thereof [application number: 202110501859.0]. The anion exchange membrane in the invention application is prepared by polymerization of methylhydroquinone, hexafluorobisphenol A and 4,4-difluorobenzophenone, and its structural formula is as follows: wherein x represents the molar ratio of methylhydroquinone to 4,4-difluorobenzophenone, which are 0.3, 0.5, 0.7 and 1.0, respectively. The cross-linking agent is 1,2-bis(4-pyridyl)ethane. The greater the molar ratio of methylhydroquinone, the more functional sites there are, and the number of cross-linking agents will also increase. And it is prepared by the following steps:
[0005] Step 1: preparing the polyetheretherketone main chain;
[0006] Step 2: subjecting the methyl groups on the polyetheretherketone main chain obtained in step 1 to bromination reaction, wherein the bromination reaction requires nitrogen protection and light protection treatment, to obtain a brominated polyetheretherketone main chain;
[0007] Step 3: adding 1,2-bis(4-pyridyl)ethane to the brominated polyetheretherketone solution of step 2 to obtain a mixed solution;
[0008] Step 4: Filter the mixed solution of step 3 and pour it into a polytetrafluoroethylene mold. After standing for 2 hours, blow dry it to obtain a cross-linked polyetheretherketone anion exchange membrane for fuel cells.
[0009] The invention patent application adopts an exchange membrane structure with polyetheretherketone as the main chain. However, these polymers will degrade in an alkaline environment, resulting in a decrease in the ion conductivity of the anion exchange membrane and a loss of mechanical strength. Conventional linear polyarylpiperidine anion exchange membranes or branched polyarylpiperidine anion exchange membranes with spatial structures, although further improving the alkaline stability of AEM, still cannot meet the requirements of long-term industrial use. Therefore, finding anion exchange membranes with good chemical stability and high conductivity is an urgent problem to be solved. Summary of the invention
[0010] The object of the present invention is to provide a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell in view of the above problems.
[0011] Another object of the present invention is to provide a method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell in view of the above problems.
[0012] In order to achieve the above object, the present invention adopts the following technical solutions:
[0013] A cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, wherein the polymer structure of the anion exchange membrane comprises a branched group polymerization unit containing a piperidine structure and a linear structure polymerization unit containing a piperidine structure, and the polymers are cross-linked through the cross-linking group polymerization unit;
[0014] The cross-linking group polymerization unit has a structure shown in the following formula I:
[0015]
[0016] (Formula I)
[0017] The branched group polymerization unit containing a piperidine structure has a structure shown in the following formula II:
[0018]
[0019] (Formula II)
[0020] The linear structure polymerization unit containing a piperidine structure has a structure shown in the following formula III:
[0021]
[0022] (Formula III)
[0023] Specifically, the polymer has a structure as shown in the following formula:
[0024]
[0025] or,
[0026]
[0027] or,
[0028]
[0029] in,
[0030] Ar1 is a phenyl structure monomer with a branched group, and the molar proportion of the branched group polymerization unit in the polymer is x, in units of %;
[0031] Ar2 is a linear phenyl structure monomer, and the molar proportion of the linear structure polymerization unit in the polymer is y, and the unit is %;
[0032] x+y=100%;
[0033] z is the degree of crosslinking of the polymer through the crosslinking group polymerization unit, z is 10-50%;
[0034] The degree of polymerization n of the cross-linking group polymerization unit is in the range of 1<n≤40.
[0035] In the above-mentioned cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the Ar1 includes at least one of the phenyl structural monomers of the following structures:
[0036] .
[0037] In the above-mentioned cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the Ar2 comprises at least one of the phenyl structural monomers of the following structures:
[0038] .
[0039] In the above-mentioned cross-linked piperidine anion exchange membrane for alkaline electrolytic cell, the molar ratio of the branched group phenyl structure monomer Ar1 to the linear structure phenyl structure monomer Ar2 is 1:5-30.
[0040] A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell comprises the following steps:
[0041] Step 1: adding branched group phenyl structure monomer Ar1, linear structure phenyl structure monomer Ar2 and N-methyl-4-piperidone monomer to a first solvent and mixing, and performing polymerization reaction in the presence of a catalyst;
[0042] Step 2: adding the reaction solution after the reaction into a second solvent to precipitate a crude polymer, and then washing and drying the crude polymer;
[0043] Step 3: adding the dried polymer crude product to the third solvent, adding iodomethane and p-chloromethylstyrene after dissolution, and finally adding potassium carbonate, reacting for 36-48 hours under light-proof conditions, pouring the solution after the reaction into the fourth solvent for precipitation, and finally washing with the fourth solvent, filtering and drying to obtain a quaternary ammonium polymer;
[0044] Step 4: dissolving the quaternized polymer and the initiator in the fifth solvent, filtering after dissolution to obtain a casting solution, casting the casting solution into a membrane, soaking the membrane in a potassium hydroxide solution for 24-48 hours, and then soaking it in deionized water until neutral, to obtain a cross-linked piperidine anion exchange membrane.
[0045] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the first solvent comprises at least one of dichloromethane, chloroform and tetrahydrofuran.
[0046] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the second solvent comprises at least one of ethyl acetate, methanol, ethanol, diethyl ether, tetrahydrofuran and acetone.
[0047] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the third solvent includes at least one of ethyl N-methylpyrrolidone and dimethyl sulfoxide.
[0048] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the fourth solvent includes at least one of acetone and ethyl acetate.
[0049] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the fifth solvent includes at least one of N-methylpyrrolidone and dimethyl sulfoxide.
[0050] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid.
[0051] In the above-mentioned method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the molar ratio of the trifluoroacetic acid to the N-methyl-4-piperidone monomer is 1-2:1, or the molar ratio of the trifluoromethanesulfonic acid to the N-methyl-4-piperidone monomer is 10-20:1.
[0052] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the initiator includes at least one of benzoyl peroxide, dilauroyl peroxide and azobisisobutyronitrile.
[0053] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the volume ratio of the first solvent to the second solvent is 1:10-30.
[0054] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the amount of the N-methyl-4-piperidone monomer added based on the first solvent is 10-22.5 mmol of the N-methyl-4-piperidone monomer per 10-15 mL of the first solvent;
[0055] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the molar ratio of the dried crude polymer: methyl iodide: p-chloromethylstyrene: potassium carbonate is 1:1.5-2:0.2-0.6:0.5-1;
[0056] In the above method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, the molar ratio of the initiator to p-chloromethylstyrene is 2-7:1000.
[0057] Compared with the prior art, the advantages of the present invention are:
[0058] 1. The present invention provides a new main chain structure composed of a branched group polymerization unit containing a piperidine structure and a linear structure polymerization unit containing a piperidine structure, and uses a cross-linking group polymerization unit for cross-linking. The polysulfone and polyetheretherketone commonly used in the prior art are not used as the main chain. At the same time, the branched group polymerization unit has multiple piperidine structures, which further increases the content of the piperidine structure in the main chain structure, so that it has better chemical stability.
[0059] 2. The present invention controls the polymer main chain structure by controlling the feeding ratio of the monomers, and then reacts the polymer with a quaternary ammonium agent, i.e., a mixture of methyl iodide and p-chloromethylstyrene, to obtain a quaternary ammonium polymer, and the quaternary ammonium polymer is mixed with an initiator for film casting. The prepared film has good chemical stability and high conductivity, and can meet the requirements of long-term use of alkaline electrolytic cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 is the NMR characterization spectrum of the quaternary ammonium polymer prepared in Example 3;
[0061] Figure 2 The water absorption rate and swelling rate of the anion exchange membrane prepared in Example 3 at different temperatures;
[0062] Figure 3 The water absorption rate and swelling rate of the anion exchange membrane prepared in Example 1-3 at 80°C;
[0063] Figure 4 This is a test diagram of the polarization curve of the anion exchange membrane prepared in Example 3;
[0064] Figure 5 This is the impedance test diagram of the anion exchange membrane prepared in Example 3. DETAILED DESCRIPTION
[0065] The present invention will be further described in detail below with reference to the accompanying drawings and specific implementation methods.
[0066] Example 1
[0067] This embodiment provides a method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell:
[0068] 82.876g (359.8mmol) of p-terphenyl and 82.876g (359.8mmol) of m-terphenyl were added to a 2000mL jacketed reactor, followed by 582.7ml of dichloromethane solution, followed by 114.231g (1009.5mmol) of N-methyl-4-piperidone and 11.606g (37.9mmol) of 1,3,5-triphenylbenzene. After mechanical stirring for a period of time, 89.2mL (1164.8mmol) of trifluoroacetic acid and 1030.7mL (11.648mol) of trifluoromethanesulfonic acid were slowly added under ice bath conditions, and 0°C was maintained during the reaction. The reaction took 6 hours, and when the solution became highly viscous, the reaction solution was poured into methanol to precipitate the crude polymer, which was then washed with deionized water until neutral and dried at 60°C for 24h to obtain a branched piperidine polymer.
[0069] Quaternization reaction: Weigh 100g (309.1mmol) of branched piperidine polymer and add it to a 2000mL single-mouth flat-bottom flask, then add 1500mL N-methylpyrrolidone, mix and then add 34.171g (247.2mmol) potassium carbonate, 9.432g (61.8mmol) p-chloromethylstyrene and 65.801g (463.6mmol) methyl iodide, react at room temperature in the dark for about 48h, after the reaction is completed, pour the obtained solution into ethyl acetate to precipitate solid powder product, filter and dry, wash with deionized water several times to remove unreacted salt, dry at 60℃ for 24h to obtain quaternized polymer. Weigh 144.2g of quaternized polymer and 0.044g (0.182mmol) BPO and dissolve them in 2884mL dimethyl sulfoxide, centrifuge the casting solution and cast it in a glass mold, dry at 60℃ for 24h to obtain a cross-linked polymer membrane. The cross-linked polymer membrane was immersed in a 1 mol / L NaOH solution at room temperature for 24 hours, and then repeatedly washed with deionized water and immersed for 24 hours until neutral, thereby obtaining a cross-linked piperidine anion exchange membrane.
[0070] Example 2
[0071] This embodiment provides a method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, and the method steps are basically the same as those in Example 1, except that:
[0072] The amount of p-terphenyl was adjusted to 52.343 g (227.3 mmol), the amount of m-terphenyl was adjusted to 113.409 g (492.4 mmol), and the amount of p-chloromethylstyrene was adjusted to 14.149 g (92.7 mmol).
[0073] Example 3
[0074] This embodiment provides a method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, and the method steps are basically the same as those in Example 1, except that:
[0075] The amount of p-terphenyl was adjusted to 26.171 g (113.6 mmol), the amount of m-terphenyl was adjusted to 139.581 g (606 mmol), and the amount of p-chloromethylstyrene was adjusted to 18.865 g (123.6 mmol).
[0076] The structural formula of the Ar1 monomer in this embodiment is:
[0077]
[0078] The structural formula of Ar2 monomer is:
[0079] and
[0080] The obtained anion exchange membrane structural formula is:
[0081]
[0082] Among them, n=17.
[0083] Application Example 1
[0084] The quaternized polymer prepared in Example 3 was characterized by NMR. Its structural formula is as follows:
[0085]
[0086] The quaternary ammonium polymer prepared in Example 3 has a hydrogen nuclear magnetic resonance spectrum measured by a Bruker 600 MHz nuclear magnetic resonance spectrometer using deuterated dimethyl sulfoxide as a deuterated reagent. Figure 1 shown.
[0087] Application Example 2
[0088] Water absorption and swelling test.
[0089] The anion exchange membranes prepared in Example 1, Example 2 and Example 3 were taken, and the water absorption rate and swelling rate of the obtained membranes were tested.
[0090] The cross-linked anion exchange membrane was soaked in deionized water at different temperatures to achieve adsorption equilibrium. After the surface water was dried, the weight (Wwet) and length (Lwet) of the wet sample were measured. The membrane was then dried in a vacuum oven at 80°C for 24 hours to measure the weight (Wdry) and length (Ldry) of each membrane in a dry state. The water absorption rate and swelling rate were calculated by the following formula:
[0091]
[0092]
[0093] Attached Figure 2 The water absorption rate and swelling rate of the anion exchange membrane prepared in Example 3 at different temperatures;
[0094] Attached Figure 3 is the water absorption rate and swelling rate of the anion exchange membrane prepared in Example 1-3 at 80°C;
[0095] By the attached Figure 2 The results show that the OH of the low swelling, low water absorption polyaryl methyl piperidine copolymer prepared in Example 3 -The water absorption and swelling rate of the anion exchange membrane at different temperatures (30, 40, 50, 60, 70, 80°C). Among them, at 80°C, the water absorption rate is 23.58%, <30%, and the swelling rate is 8.78%, <10%. It can be seen that the membrane of the present invention has a lower water absorption and swelling rate.
[0096] By the attached Figure 3 It can be seen that with the increase of cross-linking degree, the water absorption and swelling rate are greatly improved.
[0097] Application Example 3
[0098] Polarization curve test.
[0099] Test conditions:
[0100] Electrolyte: 1M KOH, test temperature: electrolyte temperature 60℃, electrolytic cell body 60℃; membrane electrode area: 2*2cm 2 .
[0101] Conventional instruments and accessories for testing:
[0102] Peristaltic pump: Kanmoer UIP S253; Pump tube: BPT 4.8*8mm; Electrolyzer (bipolar plate): N6 high-purity nickel plate (flow field area: 2.5*2.5cm²); Heater: Lichen HH-2 water bath; Test power supply: NGI-N36150-20-100.
[0103] Figure 4 This is a test diagram of the polarization curve of the anion exchange membrane prepared in Example 3;
[0104] Figure 5 This is the impedance test diagram of the anion exchange membrane prepared in Example 3.
[0105] Depend on Figure 4 , Figure 5 It can be seen that the film prepared by the present invention has lower surface resistance and better performance.
[0106] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.
Claims
1. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell, characterized in that: The following steps are involved: Step 1: adding branched group phenyl structure monomer Ar1, linear structure phenyl structure monomer Ar2 and N-methyl-4-piperidone monomer to a first solvent and mixing, and performing polymerization reaction in the presence of a catalyst; Step 2: adding the reaction solution after the reaction into a second solvent to precipitate a crude polymer, and then washing and drying the crude polymer; Step 3: adding the dried polymer crude product to the third solvent, adding iodomethane and p-chloromethylstyrene after dissolution, and finally adding potassium carbonate, reacting for 36-48 hours under light-proof conditions, pouring the solution after the reaction into the fourth solvent for precipitation, and finally washing with the fourth solvent, filtering and drying to obtain a quaternary ammonium polymer; Step 4: dissolving the quaternized polymer and the initiator in the fifth solvent, filtering after dissolution to obtain a casting solution, casting the casting solution into a membrane, soaking the membrane in a potassium hydroxide solution for 24-48 hours, and then soaking it in deionized water until neutral, to obtain a cross-linked piperidine anion exchange membrane; The Ar1 includes at least one of the phenyl structural monomers of the following structures: The Ar2 comprises at least one of the phenyl structural monomers of the following structures: 。 2. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell as claimed in claim 1, characterized in that: The first solvent includes at least one of dichloromethane, chloroform and tetrahydrofuran.
3. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell as claimed in claim 1, characterized in that: The second solvent includes at least one of ethyl acetate, methanol, ethanol, diethyl ether, tetrahydrofuran and acetone.
4. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell as claimed in claim 1, characterized in that: The third solvent includes at least one of N-methylpyrrolidone and dimethyl sulfoxide.
5. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The fourth solvent includes at least one of acetone and ethyl acetate.
6. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The fifth solvent includes at least one of N-methylpyrrolidone and dimethyl sulfoxide.
7. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The catalyst is trifluoroacetic acid and / or trifluoromethanesulfonic acid.
8. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 7, characterized in that: The molar ratio of the trifluoroacetic acid to the N-methyl-4-piperidone monomer is 1-2:1, or the molar ratio of the trifluoromethanesulfonic acid to the N-methyl-4-piperidone monomer is 10-20:
1.
9. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The initiator includes at least one of benzoyl peroxide, dilauroyl peroxide and azobisisobutyronitrile.
10. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The volume ratio of the first solvent to the second solvent is 1:10-30.
11. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The amount of the N-methyl-4-piperidone monomer added based on the first solvent is 10-22.5 mmol of the N-methyl-4-piperidone monomer per 10-15 mL of the first solvent.
12. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The molar ratio of the dried polymer crude product: methyl iodide: p-chloromethylstyrene: potassium carbonate is 1:1.5-2:0.2-0.6:0.5-1.
13. A method for preparing a cross-linked piperidine anion exchange membrane for an alkaline electrolytic cell according to claim 1, characterized in that: The molar ratio of the initiator to p-chloromethylstyrene is 2-7:1000.
Citation Information
Patent Citations
Cross-linked polyether-ether-ketone anion exchange membrane for fuel cell and preparation method thereof
CN113429561A
Piperidine type anion exchange membrane for alkaline electrolytic tank and preparation method thereof
CN112608503A
Branched polyaryl piperidine polymer and anion exchange membrane
CN115521445A
Preparation method and application of cross-linked anion exchange membrane
CN115548397A
Ether-containing piperidine anion exchange membrane, preparation method and application
CN115627001A
